Good Reasons Sell: Reason-Based Choice Among Group and Individual Investors in the Stock Market - Barber, Brad M.; Heath, Chip; Odean, Terrance (Management Science, 2003)
In this paper, we compare the investment decisions of groups (stock clubs) and individuals. Both individuals and clubs are more likely to purchase stocks that are associated with good reasons (e.g., a company that is featured on a list of most-admired companies). However, stock clubs favor such stocks more than individuals, despite the fact that such reasons do not improve performance. We describe why social dynamics may make good reasons more important for groups than individuals.